The Concept of Tolerance in Judaism, Christianity and Islam - Rachik, Catharina 19XX-; Tamer, Georges (Key Concepts in Interreligious Discourses, 2025)
Tolerance as a universal value of modernity is not usually associated in popular consciousness with religion, which is often regarded as inherently intolerant. This volume addresses the hermeneutics of tolerance as it pertains to Judaism, Christianity, and Islam. Each author offers a distinctive theological interpretation of traditional sources, elucidating the potential and limitations of tolerance in the monotheistic thought. Additionally, the book presents examinations of the promotion of tolerance in diverse historical and cultural contexts, illustrating both similarities and differences between the three religions. The evidence presented in this volume demonstrates that tolerance occupies an important place in Judaism, Christianity, and Islam